2016
DOI: 10.1007/s00774-016-0780-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the sensory neurotransmitter calcitonin gene-related peptide on bone marrow mesenchymal stem cells from ovariectomized rats

Abstract: In order to explore the effects of calcitonin gene-related peptide (CGRP) on bone mesenchymal stem cells (BMSCs) from ovariectomized (OVX) rats, an OVX rat model was used. An ELISA was performed to examine the changes in CGRP level in the plasma and skeleton. The BMSCs from the sham rats were designated group A. The BMSCs from the OVX rats (groups B, C, D and E) were treated with different concentrations of CGRP (10, 10, 10 and 0 M) in vitro. The proliferation and osteogenic and adipogenic differentiation pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…(32) Chen et al reported that 10 − 6 -10 − 10 M CGRP promoted proliferation of bone marrow MSCs in a dose-dependent manner and that CGRP played a role in adjusting bone mass and strength in ovariectomized rats. (33) In the current study, HGF signal intensity was also correlated with colony number per dish in 7 donors, and HGF promoted migration of synovial uid MSCs. HGF is secreted by mesenchymal cells and has effects for morphogenesis, angiogenesis, in ammation, tissue repair, etc.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…(32) Chen et al reported that 10 − 6 -10 − 10 M CGRP promoted proliferation of bone marrow MSCs in a dose-dependent manner and that CGRP played a role in adjusting bone mass and strength in ovariectomized rats. (33) In the current study, HGF signal intensity was also correlated with colony number per dish in 7 donors, and HGF promoted migration of synovial uid MSCs. HGF is secreted by mesenchymal cells and has effects for morphogenesis, angiogenesis, in ammation, tissue repair, etc.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, these factors have already been reported to promote the migration of MSCs, though they were not found to derive from synovium. (32,33) This suggests that other factors that showed a high relationship between the MSC number and protein concentration in the synovial uid might also promote the migration of synovial uid MSCs in the migration assay we performed.…”
Section: Discussionmentioning
confidence: 91%
“…Unmyelinated sensory neurons contain a variety of transmitter peptides, such as CGRP and SP. CGRP has been reported to inhibit osteoclastogenesis [36] and bone resorption [37] and to stimulate osteoblasts proliferation and bone formation [38] , [39] . SP could stimulate osteoclast resorption and is involved in the pathogenesis of bone changes [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that capsaicin-sensitive sensory nerve fibers were CGRP-positive nerve fibers [17]. In addition, it has been reported that when regular capsaicin treatment is applied CGRPpositive nerve fibers are depleted, bone formation is inhibited and bone resorption is increased [35].…”
Section: Discussionmentioning
confidence: 99%